No Association between Single-Nucleotide Polymorphisms of The S1PR1 Gene or Interleukin-17 Levels with Fingolimod Response in A Small Group of Iranian Relapsing-Remitting Multiple Sclerosis Patients: A Case-Control Study - Nasrin Moheghi; Payam Sasannezhad; Andrew John Walley (Cell Journal, 2024)
Objective: Multiple sclerosis (MS) has a multi-factorial etiology involving genetic factors. Fingolimod (Gilenya ®,FTY720) modulates the G-protein-coupled sphingosine 1-phosphate (S1P) receptors, S1PR1, 2, 3, 4 and 5. Variationin the human S1PR1 coding sequence results in heterogeneity in the function of the receptor. Interleukin-17, producingCD4+ T cells, tends to be increased after treatment with Fingolimod. The aim of the study was to investigate single-nucleotidepolymorphisms (SNPs) in the S1PR1 gene or interleukin-17 (IL-17) levels in a small group of Iranian relapsing-remittingMS patients treated with Fingolimod.Materials and Methods: In this case-control study, the genomic DNA of 94 MS patients treated with Fingolimod wasextracted and Sanger sequencing was performed on polymerase chain reaction (PCR) products to detect variants inthe S1PR1 gene. Quantification of IL-17 from the serum of the patients was performed using a commercially availableenzyme-linked immunosorbent assay (ELISA).Results: Among 94 relapsing-remitting MS patients treated with Fingolimod, 69 (73.4%) were responders and 25(26.6%) were non-responders. There were four novel and five common SNPs in the S1PR1 gene and no significantassociation between SNP genotype and drug response was detected. In a subset of 34 patients, there was no significantdifference in IL-17 serum concentrations before or after treatment and no association with S1PR1 polymorphisms wasdetermined.Conclusion: This study is the first in Iran to investigate association between SNPs of the S1PR1 gene or IL-17 levelswith fingolimod response in a small group of Iranian relapsing remitting MS patients. There was no association withS1PR1 gene SNPs or IL-17 levels before or after treatment.